O movimento escoteiro e as contribuições da educação não formal para o ensino de geografia e cartografia - Sabota, Heitor Silva (2014)
This paper refers to the contributions and colaborations of non-formal education to the formal knowlodge of Geography and Cartography. For that, it was realized a Participant research in Scouting and in the State Public Education. This investigation ocurred between 2012 and 2013, in Goiânia-GO, at Escoteiro Goias group and at Carlos Alberto de Deus State College. The research discuss how the adoption of methodologies, which involves the apprentice's routine, affects directly the process of construction of the cartography and geography knowledge. The gold of the paper was investigate the contributions of the scouting to the Geography knowledge using teaching strategies used by the movement, turned to the understanding of the physical space and the Cartographic language. To accomplish that gold, it was analyzed: the history of scouting, the theoretic grounding of the project and of the educated method of this institution and the education practices that were done. After those steps,it was also made a didactic intervention in the formal teaching, starting from the observation and systematization of three scouting activities that presented significant efficiency in the mediation of topics and Geographic and Cartographic's definitions. After the pedagogical practice, we could see the well results of the students, where the ones who participated on the research could build and relate the knowledge learned with the routine practice.